Jurisprudential Rulings Related to Nosebleeds in Purity and Prayer and its Impact on Worships A Comparative Jurisprudential Study - Jassim , Mohammed (Islamic Sciences Journal, 2023)
Nosebleeds, which is the blood that comes out of the nose, is considered one of the rulings on which the jurists differed .This blood is considered unclean, and it is included in all acts of worship, including purification, prayer, fasting and Hajj. So this research is limited to the section on purity and prayer only. I presented the difference between jurists in the ruling on nosebleeds in prayer, and how they have different points of view in that the nosebleed is for ablution of prayer or not?. I clarified the preponderant opinions about it, and divided my research into an introduction a preface and two topics. The preface included definition of the research vocabulary. The first topic included the rule of nosebleed in purity, and included three demands. The second topic included the rule of nosebleed in prayer, and included two demands,. The research concluded with a conclusion that included the most important results, and then included them with a list of sources and references.